MOLECULAR AND METABOLIC ASPECTS OF MALE INFERTILITY - V. N. Pavlov; E. F. Galimova; B. F. Teregulov; V. T. Kaybishev; Sh. N. Galimov (Вестник урологии)
In a review on the basis of own and literary data the molecular and metabolic conditions of idiopathic infertility in men are considered. Key features of the metabolism and energy in the ejaculate are revealed. Cause-and-effect relationship between the parameters of seminal plasma metabolism and morphofunctional characteristics of spermatozoa, the violation of which is accompanied by a reduction in fertility potential are described. The necessity of increasing scientific research in this field in order to optimize the search of molecular targets and the development of targeted therapy of male infertility is substantiated.